2012
DOI: 10.1016/j.archoralbio.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of nanoemulsion on cariogenic planktonic and biofilm organisms

Abstract: Introduction Nanoemulsions (NE) are a unique class of disinfectants produced by mixing a water immiscible liquid phase into an aqueous phase under high shear forces. NE have antimicrobial properties and are also effective anti-biofilm agents. Materials and Methods The effectiveness of nanoemulsion and its components was determined against Streptococcus mutans and Lactobacillus casei by live/dead staining. In vitro antimicrobial effectiveness of nanoemulsion against planktonic Streptococcus mutans, Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 33 publications
(40 reference statements)
2
36
0
1
Order By: Relevance
“…16,17 Recently, alternatives that might offer the possibility for efficient reduction of cariogenic microorganisms and, consequently, make a feasible control of dental caries are being sought. [18][19][20][21] Under these circumstances, photodynamic therapy (PDT) may be a possible new approach for caries treatment.…”
mentioning
confidence: 99%
“…16,17 Recently, alternatives that might offer the possibility for efficient reduction of cariogenic microorganisms and, consequently, make a feasible control of dental caries are being sought. [18][19][20][21] Under these circumstances, photodynamic therapy (PDT) may be a possible new approach for caries treatment.…”
mentioning
confidence: 99%
“…In 2012, Ramalingam et al 168 evaluated the activity of CPC loaded onto a nanoemulsion against planktonic S. mutans, Lactobacillus casei, Actinomyces viscosus, C. albicans, and a mixed culture using microdilution technique and biofilm assay. The results demonstrated that compared to the components alone, the application of the formulation exhibited a better and enhanced activity against microorganisms, both individually and in mixed culture.…”
Section: Mes and Nanoemulsionsmentioning
confidence: 99%
“…The level of adhesion on glass surface was reduced by 94.2 to 99.5% in NE treated groups compared to positive (CHX) and negative controls. The antiadherence and anti-biofilm effects of NE suggest a promising anti-caries action [21].…”
Section: Differentmentioning
confidence: 99%